2009
DOI: 10.1177/0363546509347365
|View full text |Cite
|
Sign up to set email alerts
|

Functional Hip Characteristics of Baseball Pitchers and Position Players

Abstract: Position players may be able to develop more energy in the lower extremity, while pitchers may rely more on energy created in the core and upper extremity, potentially placing pitchers at an increased risk for upper extremity injury. These descriptive hip characteristics may help clinicians detect inadequacies and provide appropriate prevention, diagnostic, and treatment interventions for such athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
91
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 24 publications
7
91
2
Order By: Relevance
“…In a seated position, participants were asked to actively rotate the hips internally and externally while stabilizing the trunk and the hips placing their hands on the hips ( Figures 4A, B). The femur was stabilized to limit accessory motion, whereas the lower shank was rotated (internally and externally) until end ROM (11). Seated thoracic ROM assessment ( Figures 5A, B) was performed on a box (30 inches/76.2 cm high) with the hips and knees flexed at 908, and a ball (20 cm diameter) was placed between the knees to minimize motion of the lower extremities during thoracic rotation (9).…”
Section: Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a seated position, participants were asked to actively rotate the hips internally and externally while stabilizing the trunk and the hips placing their hands on the hips ( Figures 4A, B). The femur was stabilized to limit accessory motion, whereas the lower shank was rotated (internally and externally) until end ROM (11). Seated thoracic ROM assessment ( Figures 5A, B) was performed on a box (30 inches/76.2 cm high) with the hips and knees flexed at 908, and a ball (20 cm diameter) was placed between the knees to minimize motion of the lower extremities during thoracic rotation (9).…”
Section: Assessmentsmentioning
confidence: 99%
“…The ROM was then measured with the moving arm of the goniometer while maximally rotating to one side (9). A digital inclinometer measuring angular position/displacement over the full 3608 with respect to the vertical axis was used for the hip rotation ROM assessment (11).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The importance of the kinetic chain is well accepted, yet research examining its effect on shoulder injury, specifically hip ROM and strength, is limited to adult populations. 4,12,13 The hips play an important role in the throwing motion; effective lead-leg ROM is necessary to generate force through the upper extremity to produce greater ball velocity. 13,14 Investigation suggests a relationship between hip and shoulder ROM and shoulder injury; however, this relationship has not been found in healthy professional baseball athletes.…”
mentioning
confidence: 99%
“…4,12,13 The hips play an important role in the throwing motion; effective lead-leg ROM is necessary to generate force through the upper extremity to produce greater ball velocity. 13,14 Investigation suggests a relationship between hip and shoulder ROM and shoulder injury; however, this relationship has not been found in healthy professional baseball athletes. 12 For pitchers and position athletes, Scher et al 4 found a moderate relationship between dominant-shoulder external-rotation ROM and nondominant hip-extension ROM in pitchers (r ¼ .62) and nonpitchers (r ¼ -.64) with a history of injury.…”
mentioning
confidence: 99%
“…30,34,36,37,56,61 Pathomechanics of the throwing arm have been linked to glenohumeral internal rotation deficits, high maximum pitch velocity, limited trunk and hip rotation, and improper throwing mechanics. 1,2,11,17,21,30,31,53 However, to date, no studies have examined foot arch posture as a potential risk factor for shoulder and elbow injuries in baseball pitchers.…”
mentioning
confidence: 99%